Canadian youth correctional officers' views on their work and relationships with youth in their care - Bickle, Korri (International journal of offender therapy and comparative criminology, 2024)
This study explored the personal perspectives of youth correctional officers within secure and open custody facilities in Ontario. A multi-methods design allowed for quantitative data collection to assess demographics and scores on a relationship scale and qualitative open-ended survey responses to explore areas of interest regarding officer work. Despite a small sample size (N = 26), results indicated trends in officers’ views of their work and relationships with youth. Youth officers report various job duties ranging from supervision/security to cleaning and preparing meals. Results indicate differences in endorsement for relationship development with youth for those who see treatment as part of their role in rehabilitation and those who do not. This exploratory study provides a starting point for understanding the unique experiences and duties of youth correctional officers in Ontario, Canada, and their views on relationship development with youth. Future research will include in-person interviews, facilitating more rich data collection.